Diabetes mellitus, diabetes insipidus, optic atrophy, and deafness: A case of Wolfram (DIDMOAD) syndrome - Maleki, Nasrollah (J Curr Ophthalmol, 2016)
PURPOSE: To report a case of Wolfram syndrome (WS) characterized by diabetes mellitus, diabetes insipidus, progressive optic atrophy, and deafness. CASE REPORT: A 19-year-old female patient, a known case of diabetes mellitus type I from six years before, presented with progressive vision loss since four years earlier. On fundoscopic examination, she had bilateral optic atrophy without diabetic retinopathy. The patient also had diabetes insipidus, neurosensory deafness, and neurogenic bladder. CONCLUSION: WS should be considered a differential diagnosis in patients with diabetes mellitus who present with optic atrophy, and it is necessary to perform a hearing test as well as collecting 24-h urine output.